Optimización del diseño de un Sistema de Riego por goteo para la conducción de 200 has de Arandano (vaccinium myrtillus), utilizando el Software Wcadi, en el Fundo El Remanso 2, Irrigacion Chavimochic, La Libertad - Alvarez Polo, Emilio Alejandro (2017)
The present project is presented to make known the benefits of using WCADI software in an irrigation design project for any type of crop. The synthesis of the project seeks the optimization of an irrigation project using WCADI software. To do this, the design in software vs. a common design in excel will be contrasted. The advantages and disadvantages of each design will be evaluated by taking criteria for future project cost. This means that the design of irrigation will serve if in the future want to make changes to the system is the quickest installation and with less cost per Ha. Today the most profitable crop is the blueberry (vaccinium myrtillus) which has its time of profitable cultivation, so that the irrigation systems have to be prepared for the changes that can be given in the future. One of the profiles and work of the agricultural engineer is the design of an irrigation system. But for this you have to be prepared in the software management that allow you to have many advantages in the design of an irrigation system. Agricultural engineers are increasingly using computers to rely on solving a number of problems in the design of water supply and irrigation systems. Numerous programs have been developed, mainly aimed at relieving the engineer or the tedious work of referring to tables and graphs, allowing him to elaborate a more precise plan and complete the design work in less time than was previously possible. The programs developed so far provided a non-systematic solution: they were related to specific engineering design calculations and could not formulate a fully computerized integrated irrigation design that integrates all the parameters for a project. The software, although more advanced than the previous design techniques, was cumbersome as each program addressed a specific problem in insolation without any means of linking programs. Consequently, a change in any variable at a critical design stage required an almost complete redesign of the entire system.